Risks in bank lending activity - Дорошенко, Н. О. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
This study focuses on the risks in banking. Today, commercial banks have a powerful management system, high-level automation tools, a rigid system of external control and developed risk-management. Management of credit risk lately has a special methodological interest. The purpose of the bank is to maximize profit, so it must pay particular attention to possible losses in conducting its operations. Specific types of risks that the bank most often encounters determine its performance. Since the income from lending activities makes up the most share of all revenues in the bank, the article focuses specifically on credit risk. The purpose of the research is to reveal trends in changes of the amount of credit risk of banking institutions and their influence on the stability of the banking system of Ukraine. The research of existing theoretical studies in the field of credit risk of banks, analysis of the current situation in the banking sector and solution of the following tasks: the author’s point of view on the essence of bank credit risk; improvement of the classification of credit risks of bank institutions, presentation and argumentation of the new view that takes into account the interests of both lenders and borrowers; justification of the main features of credit risks; improvement of risk management mechanism of banking institutions in lending operations as well as examination of economic standards of credit risks of Ukrainian banking institutions contributed to reaching the planned objective. The study undertaken allowed drawing a conclusion about the compliance of standards established by the National bank of Ukraine with the requirements and determining a positive trend towards stability and capitalization of the banking system on the whole. Potential directions for further researches were outlined.